Application of a Virtual Laboratory Containing Ethnoscience to Enhance Students' Critical Thinking Skills - Sari, Nella Puspita; Munawir Yusuf; Sri Yamtinah (Universitas Pendidikan Ganesha, 2023)
The ability to think critically is a basic ability that students of this century must have. This ability is also emphasized in the Independent Curriculum which is being implemented in Indonesia. However, there is a problem, namely that the school does not have a laboratory to carry out biology practical activities. Based on these problems, the aim of this research is to develop virtual laboratory learning media with ethnoscience content in biology subjects to improve students' critical thinking abilities. This research is a type of development research (R&D) that applies the ADDIE development model. The development process involves collaboration with media experts, material experts and students. The data collection method used was test instruments and questionnaires. The analytical method used is quantitative and qualitative. The results of research by media experts show that the media is suitable for use with an assessment of 92%. The results of the material expert assessment show that the content is suitable for use with an assessment of 88%. The results of the effectiveness test show a sig value of 0.000, where there is a real difference in students' critical thinking abilities before and after treatment. The results of the N gain test show that the effectiveness of learning media in improving critical thinking skills is 47%, which is included in the medium category. It is hoped that the laboratory media developed can contribute to variations in learning media that are in accordance with the Independent Curriculum, namely including elements of critical reasoning and global diversity.